DISTRIBUTION OF INJURY AND INJURY PATTERNS IN TRAUMA VICTIMS ADMITTED TO THE TRAUMA CENTRE OF CSMMU, LUCKNOW - Verma, Vikas; Singh, Sheela; Singh, Girish Kumar; Kumar, Santosh; Singh, Ajay; Gupta, Kanika (Indian Journal of Community Health, 2013)
Introduction: Understanding the characteristics of injuries, injury patterns and trauma victims is absolutely essential in ascertaining the resources required for a trauma centre. Methods: Age, sex, obesity, pre-existing chronic conditions, Injury Severity Score, Glasgow coma scale (GCS), injury type, and injury pattern were recorded. All patients admitted on all Mondays were consecutively recruited subject to informed consent. Abbreviated injury scale was used to record the type of injury. Extra burden of injury for referred patients was defined as patients who did not meet the Centre for disease control (CDC), USA criteria for admission to a trauma centre. Extra burden of injury for directly admitted patients was defined as patients that were discharged within 24 hours of admission without undergoing any operative procedure, admission to Trauma Ventilation Unit or any procedure requiring anaesthesia. Results: Eight hundred and five injuries were recorded in five hundred seventy two patients. Patients admitted on different days of the week were found to be similar. Injuries to the lower extremity were the most frequent (29%). Fractures were the most common orthopaedic injuries. Exclusive treatment by an orthopaedic surgeon or a neurosurgeon was indicated in 46.68% and 31.99% cases. The overall Extra Burden of Injury (EBI) due to a lack of organized system of trauma care was 26.04% Discussion: Majority of the EBI should have been taken care of at a district hospital as per the Indian Public Health Standard guidelines of the National rural health Mission. A vast majority of patients can be taken care of by a single specialist. Conclusion: There is significant EBI on the CSMMU trauma centre which might be responsible for higher mortality reported by previous studies. There is a need to assess whether this higher mortality is an effect of EBI.